Development of a Project-Based Student Worksheet Oriented to Local Wisdom to Enhance Creative Thinking Skills - Sri Cacik; Lilik Mawartiningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to determine the feasibility, practicality, and effectiveness of a project-based and local-wisdom-oriented student worksheet for enhancing creative thinking skills. This study is a development research employing the ADDIE model, with the research subjects being students in class C of the 2023 cohort of the Elementary School Teacher Education Study Program at Universitas PGRI Ronggolawe Tuban, totaling 32 students. This research was conducted in 2025 at Universitas PGRI Ronggolawe Tuban. The results showed that the developed student worksheet had an average feasibility score of 92%, indicating it is very feasible. The worksheet was also classified as very practical, with learning implementation and student responses reaching 93.3% and 92.9%, respectively. In addition, the worksheet demonstrated very high effectiveness in enhancing creative thinking skills, as indicated by an N-gain score of 86.88%. Based on these findings, the student worksheet integrating project-based learning and local wisdom is considered feasible, practical, and effective for enhancing students’ creative thinking skills